Pretend you're mine - Score, Lucy (Score, Lucy. Benevolence, 2023)
Luke Garrison is a hometown hero, a member of the National Guard ready to deploy again. Strong, sexy, broody, the last thing he's looking for is a woman to ruin his solitude. When the wildly beautiful Harper stumbles into his life, though, he realizes that she's the perfect decoy. A fake girlfriend to keep his family off his back until he's deployed. So what if kissing her sends his mind to wicked places? He can control himself. Can't he? Harper was on her way to starting a new life ... again. But something about Luke makes her want to settle down in this small town and make his house a home. When she's in his arms, she finally knows what it's like to feel safe. Protected. One night of sharing a bed turns into something much, much more ... and soon Luke can't keep his mind off Harper's wide gray eyes, or his hands off of her luscious curves. He never thought he'd feel this way about a woman again. But he knows that he can't tell her the truth about his dark past. And she can't reveal what she's running from. At least this isn't a real relationship. It's only for a month. It's only pretend. Until it isn't.